Pengekspresian Jatuh Cinta Siswa Sekolah Menengah Pertama Melalui Media Tulisan: Kreativitas atau Vandalisme? - Imaningtyas, Intan; Atmoko, Adi; Triyono, Triyono (Jurnal Kajian Bimbingan dan Konseling, 2017)
The purpose of this research is to understand the characteristics of falling in love and the love expression in writing media (graffiti) on Junior High School students. The chosen approach is qualitative approach with phenomenological research type. The subject is students of Sekolah Menengah Pertama Pancadarma Malang. The result shows love is expressed in the form of courting behavior, the love that underlies this relationship is romantic love so it cannot be said to be deep love (unreflective). In love expression, it can be directly (oral and action) or indirect (writing). The expression of love through writing can be classified into written media (school facilities, public facilities, private facilities, social media); writing forms (graffiti, tattoos, reply to comments, replying text messages, poetry, writing letters, short stories); and the content of writing (feelings and desires to be disclosed). It can be concluded that there are two main characteristics of the love expressed in the form of writing, the love expressed in the form of works and love expressed in the form of destructive (vandalism) behavior.